A Study on the Role of Branding In Marketing of Banking Services: Measuring and Building Strong Brand Equity in the Indian Banking Sector (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The external orientation in branding focuses on buildingstrong brand equity among customers. Developing employee based brand equity hasgained momentum in service branding literature as employees play crucial rolein facilitating brand experiences, perceptions and relationships that customersmay have with the firm. The internal brand orientation focuses on building astrong brand orientation enabling employees to understand and imbibe the brandvalues of the firm. Competitors can copy the performance of the service brandbut the intangible values such as employees‘ attachment, trust and commitmenttowards the brand, customers‘ trust and loyalty and the unique, favorableassociation towards the brand cannot be copied. This research outlines howservice brand strength can be measured by assessing the internal brand strength(employee perspective) and the external brand strength (the customerperspective) individually and provides a methodology for the same byundertaking a study on banks in India. Marketing of service firms require thedevelopment of brand experiences and unique imagery leading to the criticalrole of brand building in service firms. A strong brand scores high on brandawareness, brand service quality perceptions, and customer satisfaction. Brandscommunicate their brand name, functional benefits, inherent values and cues onbrand experiences to customers which lead to strong customer based brand equityfor the firmA strong service brand enjoys strong external as well as internalbrand equity. India was selected for the study as it is an emerging marketeconomy where the growth opportunities are considered to be large (Jin etal.,2010). Moreover the Indian service sector has grown considerably during thelast few years and has been globally recognized for its high growth anddevelopment.